2017
DOI: 10.1016/j.ssmph.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Worldviews and trust of sources for health information on electronic nicotine delivery systems: Effects on risk perceptions and use

Abstract: Public health agencies, the news media, and the tobacco/vapor industry have issued contradictory statements about the health effects of electronic nicotine delivery systems (ENDS). We investigated the levels of trust that consumers place in different information sources and how trust is associated with cultural worldviews, risk perceptions, ENDS use, and sociodemographic characteristics using a nationally representative sample of 6051 U.S. adults in 2015. Seventeen percent of adults were uncertain about their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…The scepticism may lead to continued cigarette smoking among smokers who are not ready to quit smoking. On the other hand, the use of trusted sources,29 30 38–40 statistical facts and emphasis on the known health harms of cigarettes in comparative risk messages were more compelling.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The scepticism may lead to continued cigarette smoking among smokers who are not ready to quit smoking. On the other hand, the use of trusted sources,29 30 38–40 statistical facts and emphasis on the known health harms of cigarettes in comparative risk messages were more compelling.…”
Section: Resultsmentioning
confidence: 99%
“…Participants demonstrated distrust for tobacco companies and organisations with commercial interests in tobacco products due to their knowledge of tobacco industry deception. Therefore, to decrease scepticism about the messages, the messages should mention a trusted source, such as the FDA 29 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In the same sense, Weaver et al found the highest levels of trust in information about health effects of electronic nicotine delivery systems in the providers and official health institutes versus the manufacturers, commercial sellers and media. 16 Some sites are not rigorous in providing information, which contributes to this lack of trust. A recent quality analysis of the reproducibility of one screening instrument to evaluate primary immunodeficiencies risk of disease showed significant deviations from the original instrument in several adaptations and variants published online, raising concerns about standards for scientific information.…”
Section: 13mentioning
confidence: 99%
“…Gaps may also exist between the sources participants regard as trustworthy and those they use. 22 For example, while doctors are regarded as the most reliable source of information about ENDS’ health effects, very few participants surveyed (<7%) had actually sought ENDS information from a health professional. Instead, most turned to the internet or product packaging, or sought advice from other ENDS users.…”
Section: Introductionmentioning
confidence: 99%